2020
DOI: 10.1186/s12879-020-05412-w
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of infection in newly diagnosed multiple myeloma patients: risk factors and main characteristics

Abstract: Background Infection is a leading cause of morbidity and death in patients with multiple myeloma (MM). The increased susceptibility to infection is complicated and multifactorial. However, no studies have explored the spectrum and risk factors of infections in newly diagnosed MM patients at the first admission. This cross-sectional study aimed to provide ideas for the assessment, prevention and treatment of infection in newly diagnosed MM patients when admitted for the first time. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…Accordingly, anemia was reported as a factor predisposing to various types of infections in different MM patient groups. In a cohort of newly diagnosed MM patients, Lin et al found anemia (Hgb < 90 g/L) among advanced stage (ISS III) and elevated CRP to be risk factors associated with infection [ 31 ]. The occurrence of infection also contributed to inferior survival, such as factors influencing infection occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, anemia was reported as a factor predisposing to various types of infections in different MM patient groups. In a cohort of newly diagnosed MM patients, Lin et al found anemia (Hgb < 90 g/L) among advanced stage (ISS III) and elevated CRP to be risk factors associated with infection [ 31 ]. The occurrence of infection also contributed to inferior survival, such as factors influencing infection occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, anemia was reported as a factor predisposing to various types of infections in different MM patient groups. In a cohort of newlydiagnosed MM patients, Lin et al found anemia (Hgb <9.0 g/dl), among advanced stage (ISS III) and elevated CRP to be risk factors associated with infection [33]. The occurrence of infection also contributed to inferior survival, such as factors influencing infection occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Given that NDMM patients have a high risk of infections at first admission, especially infections with Epstein‒Barr virus (EBV), hepatitis B virus (HBV) and Escherichia coli ( Lin et al, 2020 ), we excluded MM patients with concurrent infection from this study. Interestingly, our results highlight that ALI is not only an independent predictive marker of chemotherapy efficacy but also a predictor of susceptibility to infection in NDMM patients during induction chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical evidence confirms that infections represent a major cause of morbidity and mortality in patients with MM, especially for those with severe infection, pneumonia, and neutropenia in relapsed/refractory settings ( Blimark et al, 2015 ; Balmaceda et al, 2021 ). In NDMM patients admitted for the first time, risk of infection correlates with poor prognosis, particularly in those with ISS stage III or low haemoglobin levels ( Lin et al, 2020 ). MM patients with a risk of infection and complications are recommended to receive optimal preventive strategies ( Bladé and Rosiñol, 2005 ; Raje et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%